Conformism, Public News and Market Effciency. - Desgranges, G; Rochon, C (Oxford Finance, 2008)
We study the implications of conformism among analysts in a CARA Gaussian model of the market for a risky asset, where a trader's in- formation is a message sent by an analyst. Conformism increases the weight of the public information in the messages, decreasing their in- formativeness. More precise public information does not always result in more precise messages. A larger precision of the analysts informa- tion does not always make the market more liquid and the price more informative. Conformism creates an overreaction of the price to pub- lic information. Using the price as a public signal does not alter the results.